2019
DOI: 10.1177/0004865819869049
|View full text |Cite
|
Sign up to set email alerts
|

Crime and colonisation in Australia’s Torres Strait Islands

Abstract: The overrepresentation of Indigenous Australians in the criminal justice system has been thoroughly documented over a number of decades. However, studies tend to adopt homogenising discourses that fail to acknowledge or deeply examine the diversity of Indigenous Australian experiences of crime, including across geographic and cultural contexts. This has prompted calls for a more thorough investigation of how experiences of crime differ across Australia’s Indigenous communities, including between remote Aborigi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Some of this previous work has been critical and focused on the post-colonial experience (see Pratt and Melei, 2018). However, while aspects of islandness have been captured in recent work (see Scott and Morton, 2018; Staines and Scott, 2019), these studies also reinforce the idea of the island-idyll. Pratt and Melei (2018) for example, see Tuvalu as a place where customary punishments had until recently kept prison populations low, countering the dramatic growth of imprisonment in the global North.…”
Section: Anti-idyll: Towards a Critical Criminology Of Islandssupporting
confidence: 68%
“…Some of this previous work has been critical and focused on the post-colonial experience (see Pratt and Melei, 2018). However, while aspects of islandness have been captured in recent work (see Scott and Morton, 2018; Staines and Scott, 2019), these studies also reinforce the idea of the island-idyll. Pratt and Melei (2018) for example, see Tuvalu as a place where customary punishments had until recently kept prison populations low, countering the dramatic growth of imprisonment in the global North.…”
Section: Anti-idyll: Towards a Critical Criminology Of Islandssupporting
confidence: 68%
“…Scott et al (2021) argued that this history of relatively strong self-governance in the TSR, including relatively fewer destructive colonial incursions, has meant that social ties across the region are more stable, resulting in strong social bonding capital that tends to be crime protective. Staines and Scott (2020) showed that reported offences against the person and property in the TSR were lower on average between 2001 and 2018 than for remote Aboriginal communities on the Australian mainland, and that property crime was lower there than the Queensland State average. Furthermore, Scott et al (2021) argued that some justice practices in the region, such as the use of cultural mediation as a pre-court diversionary option, and the strong roles of local community justice groups comprised of community members and Elders, are also an outcome of this strong social capital, as well as serving to reinforce it.…”
Section: Australian Policing and Indigenous Peoplesmentioning
confidence: 97%
“…Other offence types were less prone to spatial differentiation. These findings have been reinforced by the continuation of remarkably different crime statistics for Indigenous communities across urban, regional and remote areas, where crime – and particularly crime against the person – is experienced in remote areas at disproportionately high rates when compared with the rest of Australia (Staines and Scott, 2020).…”
Section: Social Capital and Crimementioning
confidence: 99%
“…While Staines and Scott (2020) showed that reported crime is relatively low in the TSR and suggested relatively strong social capital (due in part, at least, to varying experiences of colonisation) may play a role, there is little empirical evidence available in the public domain that enables these possible links to be further explored. Thus, the remainder of this article considers possible explanations for lower crime rates in the TSR by drawing on empirical data collected during qualitative fieldwork in the region between 2018 and 2019.…”
Section: Torres Strait Regionmentioning
confidence: 99%
See 1 more Smart Citation